LITERASI DAN NUMERASI MENGAJAR SEBAGAI MOTIVASI DALAM PENINGKATAN MINAT BELAJAR DI DESA SUGIHARJO KEC. BATANG KUIS - Harpen Silitonga; Widya Ningsih Simalango; Lastri Marito Gurning; Selvira Yanti Harefa; Selly Lorenza Manik (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2025)
Increasing interest in learning among rural communities is a challenge in itself, especially in terms of literacy and numeracy. This study aims to analyze the role of literacy and numeracy in the teaching process as a motivational factor in increasing interest in learning in the community in Sugiharjo Village, Batang Kuis District. The method used is a qualitative approach with observation, interview, and documentation study techniques. The results of the study indicate that literacy and numeracy-based teaching strategies can increase student involvement, strengthen critical thinking skills, and build self-confidence in learning. In addition, environmental support and innovation in teaching methods play an important role in maintaining interest in learning sustainably. Thus, literacy and numeracy are not only basic skills, but also effective motivational tools in the education process at the village level.